Refined Candidate Region for F4ab/ac Enterotoxigenic Escherichia coli Susceptibility Situated Proximal to MUC13 in Pigs - Goetstouwers, Tiphanie (Public Library of Science, 2014)
F4 enterotoxigenic Escherichia coli (F4 ETEC) are an important cause of diarrhea in neonatal and newly-weaned pigs. Based on the predicted differential O-glycosylation patterns of the 2 MUC13 variants (MUC13A and MUC13B) in F4ac ETEC susceptible and F4ac ETEC resistant pigs, the MUC13 gene was recently proposed as the causal gene for F4ac ETEC susceptibility. Because the absence of MUC13 on Western blot from brush border membrane vesicles of F4ab/acR(+) pigs and the absence of F4ac attachment to immunoprecipitated MUC13 could not support this hypothesis, a new GWAS study was performed using 52 non-adhesive and 68 strong adhesive pigs for F4ab/ac ETEC originating from 5 Belgian farms. A refined candidate region (chr13: 144,810,100–144,993,222) for F4ab/ac ETEC susceptibility was identified with MUC13 adjacent to the distal part of the region. This candidate region lacks annotated genes and contains a sequence gap based on the sequence of the porcine GenomeBuild 10.2. We hypothesize that a porcine orphan gene or trans-acting element present in the identified candidate region has an effect on the glycosylation of F4 binding proteins and therefore determines the F4ab/ac ETEC susceptibility in pigs.